Study Of Association of Some Risk Factors & Cervical Dysplasia/Cancer Among Rural Women - Mhaske, Mayavati; Jawadekar , S J; Saundale , S G (National Journal of Community Medicine, 2011)
Background: At the beginning of this century, cancer was 6th cause of death in industrialized countries, today it is the second leading cause of death. Cervical cancer contributes about 25-30% of all cancer cases. Various other risk factors for cervical cancer are early age at marriage, multiparty with poor birth spacing between pregnancies, poor personal hygiene are common among the rural women, so this study is carried out to study the association of these risk factors with cervical dysplasia and cervical cancer. Aims and Objectives: 1) To study the association of these risk factors with cervical dysplasia and cervical cancer 2) To give recommendations based on study. Material and Methods: This is a cross-sectional study carried among the rural women in Beed district .All the married women undergoing pap smear were interviewed and pretested proforma was filled and pap smear were taken. Results: out of total 462 women 399 (86.4%) were married before 17 yr of age and prevalence of dysplasia is about 19.04%among the women married before 17yrs. Of age and about 7.94 among the women married after 17yr of age. of the total 81 women 74 had their I st child before 20yrs of age,26.31% women had more than four children and dysplasia was common in lower socioeconomic group. Conclusion: present study highlights the significant association between risk factors so there is need to reduce these risk factors among rural women.